FAKTOR-FAKTOR YANG MEMPENGARUHI STOK BERAS DI SUMATERA SELATAN - Taufiq Marwa; Eka Rostartina; Abu Kosim (Department of Development Economics, Universitas Sriwijaya, 2009)
This study aims to analyze the influence of the level of producer prices of rice, retail prices of rice, imported rice, rice production, population, and the stock of the previous year of rice stocks are controlled by the government. The data used are secondary data obtained from relevant agencies. These results indicate that together the variable price of rice in rural markets, retail rice prices, variable import rice production variables, population variables and the stock of the previous year significantly affect the stock of government-controlled rice. Varied 53.9 percent free variables is determined by the varied value of free variable. Partially significant variable affecting rice stocks is the variable controlled rice imports and population, while the other variables are not significant. Response of rice stocks to the variables that affect relatively similar, both in the short and long term Key Words: Stock owned, retail prices, farm gate prices, imports of rice